Geisha, harlot, strangler, star : a woman, sex, and morality in modern Japan - Johnston, William, 1955- (Asia perspectives., 2005)
In May 1936, Abe Sada committed the most notorious crime in twentieth-century Japan -- the murder and emasculation of her lover. What made her do it? And why was she found guilty of murder yet sentenced to only six years in prison? Why have this woman and her crime remained so famous for so long, and what does her fame have to say about attitudes toward sex and sexuality in modern Japan? Despite Abe Sada's notoriety and the depictions of her in film and fiction (notably in the classic In the Realm of the Senses), until now, there have been no books written in English that examine her life and the forces that pushed her to commit the crime. Along with a detailed account of Sada's personal history, the events leading up to the murder, and its aftermath, this books contains transcripts of the policy interrogations after her arrest--one of the few existing first-person records of a woman who worked in the Japanese sex industry during the 1920s and 1930s--as well as a memoir by the judge and police records.